2018
DOI: 10.1080/21645515.2018.1426419
|View full text |Cite
|
Sign up to set email alerts
|

The effects of booster vaccination of hepatitis B vaccine on children 5–15 years after primary immunization: A 5-year follow-up study

Abstract: The aim of this study was to evaluate changes in hepatitis B surface antibody titers (anti-HBs) after booster vaccinations in children aged 5-15 y and to provide suitable immunization strategies. A total of 2208 children were initially enrolled in screening, and 559 children were finally included. The participants were divided into 2 groups according to their pre-booster anti-HBs levels: Group I, <10 mIU/ml and Group II, ≥10 mIU/ml. Group I was administered 3 doses of booster hepatitis B vaccine (0-1-6 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In addition, antibody titers steadily decreased with age, while infectionrelated immunity increased. Although women were in the majority in our study, there was no association between gender and HepB immune response, which was consistent with previous studies (17,20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, antibody titers steadily decreased with age, while infectionrelated immunity increased. Although women were in the majority in our study, there was no association between gender and HepB immune response, which was consistent with previous studies (17,20).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, after giving HepB vaccine at birth, the protective immune response was lost in 10% of the Taiwanese adolescent population (16). This may be associated with loss of immunologic memory, attenuation of anti-HBs, and increased risk of transmission (17). An anti-HBs titer of ≥ 10 mIU/mL is considered protective against HBV infection (18), and reduced vaccine immunity is of concern as it could lead to an outbreak of hepatitis infection and put an entire population at risk.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in anti-HBs antibodies over time below the seroprotection threshold is a controversial issue. Several studies have shown that individuals with aHBs levels between 1 and 9.99 mIU/mL quickly recover seroprotective aHBs levels after receiving a booster [19][20][21][22], due to immune memory [23,24]. In this context, the available bibliography widely reports that individuals with aHBs levels between 1 and 9.99 mIU/mL mostly generate an adequate anamnestic response and, therefore, are considered protected against HBV infection [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…HBV is highly infectious, transmitted through blood or sexual contact, and is estimated to affect nearly 300 million people worldwide, causing more than 800 000 deaths annually, most of which are due to cirrhosis and hepatocellular carcinoma. , The traditional and effective strategy to prevent HBV infection is vaccination against hepatitis B. However, three doses of hepatitis B vaccine according to the routine vaccination schedule at 0, 1, and 6 months in healthy populations still produce no hepattis B surface antibody (anti-HBs) or produce anti-HBs at titers <10 U/L in 5% to 10% of vaccinated individuals with a nonresponsive status. , …”
Section: Advances In the Clinical Application Of Cancer Vaccinesmentioning
confidence: 99%